Current knowledge on evidence-based shockwave treatments for shoulder pathology. (December 2015) - Moya, Daniel; Ramón, Silvia; Guiloff, Leonardo; Gerdesmeyer, Ludger
Abstract: Shoulder pain is one of the most common musculoskeletal pathologies. Treatment by ESWT (extracorporeal shockwave therapy) has emerged as an alternative when conservative treatment fails in rotator cuff calcific tendinopathy, prior to invasive procedures. The clinical efficacy of ESWT in non-calcific tendinopathy remains controversial. The good results in the treatment of rotator cuff calcifications, have led to indications of ESWT being expanded to other shoulder pathologies. We review the current state of indications and evidence based practice. Highlights: We present the current knowledge on shockwave treatments for shoulder pathology. ESWT is an efficient tool for the treatment of rotator cuff calcifications. The clinical efficacy of ESWT in non-calcific tendinopathies is controversial. Promising results have been reported on other shoulder pathologies.